Implementation of the Improvement of the Qur'an Literacy Program for Modern Boarding School Students - Moh Ali Fauzi; Tri Diana Kusuma Baskari; Riza Ashari; Yuli Marlina; Riza Faishol (STAI Miftahul Ula Nganjuk, 2025)
This study aims to explore the implementation of the Al-Qur'an reading and writing program at Pondok Modern Al-Barokah Ngepung Patianrowo, focusing on enhancing the literacy skills of its students. The research employs a descriptive qualitative method, with the second grade of KMI as the sample group. Data was collected through interviews, observations, and documentation. The study found that the students' pronunciation of Arabic letters is emphasized, particularly through the application of tajweed rules, direct reading practice in front of teachers, and the use of methods such as lectures, drills, assignments, and the traditional sorogan approach. The implementation of the program takes approximately six months, allowing for individual assessment of students' fluency in reading the Qur'an. This timeframe is necessary to ensure the students' proficiency in Qur'anic literacy.